The Effectiveness of Rational Emotive Behavior Therapy Group Counseling in Reducing Fear of Missing Out (FoMO) Among University Students - Amallia Putri (Universitas PGRI Yogyakarta, 2026)
Mental health issues among university students have become a growing concern, with Fear of Missing Out (FoMO) emerging as a significant psychological challenge in the digital age. FoMO is characterized by anxiety over missing valuable experiences, often exacerbated by excessive social media engagement, and has been linked to decreased well-being, sleep disturbances, and reduced academic focus. This study aims to investigate the effectiveness of group counseling using the Rational Emotive Behavior Therapy (REBT) approach in reducing FoMO among university students. A pre-experimental one-group pretest-posttest design was employed, involving eight students from the Guidance and Counseling Study Program, Faculty of Teacher Training and Education, Tanjungpura University, selected through purposive sampling based on high FoMO scores. The intervention consisted of five REBT-based group counseling sessions, each lasting 60–90 minutes, focusing on identifying and restructuring irrational beliefs underlying FoMO-related behaviors. The Fear of Missing Out scale, developed by Przybylski et al. (2013), was administered before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test. Results showed a significant reduction in FoMO levels following the intervention, with a Z value of -2.524 and a p-value of 0.012 (p < 0.05), indicating that REBT-based group counseling effectively reduces FoMO. These findings suggest that REBT group counseling can serve as a valuable intervention for addressing FoMO and improving students' psychological well-being. This study contributes to the growing body of evidence supporting REBT as a therapeutic approach for digital-age psychological challenges and highlights the importance of integrating such interventions into university counseling services. Keywords: fear of missing out, group counselling, rational emotive behavior therapy, university students, mental health